2020
DOI: 10.4314/ijbcs.v14i5.19
|View full text |Cite
|
Sign up to set email alerts
|

Land use/land cover patterns and challenges to sustainable management of the Mono transboundary biosphere reserve between Togo and Benin, West Africa

Abstract: The Mono Transboundary Biosphere Reserve (RBTM) has significant resources but faces many threats that lead to habitat fragmentation and reduction of ecosystem services. This study, based on satellite image analysis and processing, was carried out to establish the baseline of land cover and land use status and to analyze their dynamics over the period 1986 to 2015. The baseline of land cover established six categories of land use including wetlands (45.11%), mosaic crops/fallow (25.99%), savannas (17.04%), plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 23 publications
1
13
0
4
Order By: Relevance
“…In the study area, the top-down approach to resource management implemented prior to the creation of the MTBR has failed to effectively conserve mangroves in the area. This is reported by Adjonou et al, (2020) who observed that over 93% of mangroves and wetlands in the area were lost from 1980 to 2015. The comanagement adopted following the creation of the reserve is expected to promote mangrove reforestation, curb human-induced mangrove degradation and promote mangrove sustainable use in the reserve (Ecobenin, 2017).…”
Section: Co-management Framework In the Mtbrmentioning
confidence: 73%
See 1 more Smart Citation
“…In the study area, the top-down approach to resource management implemented prior to the creation of the MTBR has failed to effectively conserve mangroves in the area. This is reported by Adjonou et al, (2020) who observed that over 93% of mangroves and wetlands in the area were lost from 1980 to 2015. The comanagement adopted following the creation of the reserve is expected to promote mangrove reforestation, curb human-induced mangrove degradation and promote mangrove sustainable use in the reserve (Ecobenin, 2017).…”
Section: Co-management Framework In the Mtbrmentioning
confidence: 73%
“…Indeed, it takes decades for mangrove ecosystems to bounce back to normal if they undergo serious disturbances. This the case in the area prior to the establishment of the reserve in 2017 (Adjonou et al, 2020;Teka et al, 2018). This necessitates a lot of restoration and conservation efforts currently underway within the reserve with the support of many international institutions (Guelly et al, 2020).…”
Section: Discussionmentioning
confidence: 98%
“…Studies revealed that it takes decades for mangrove ecosystems to bounce back to normal if they undergo serious disturbances. This was the case in the area prior to the establishment of the reserve in 2017 (Adjonou et al 2020;Teka et al 2019). This necessitates a lot of restoration and conservation efforts currently underway within the reserve with the support of many international institutions (Guelly et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…After the creation of the reserve in 2017, decision-makers agreed on the implementation of the co-management approach. Therefore, the management of all the natural resources of the reserve was decentralized, with the active participation of the local communities (Adjonou et al 2020). Prior to the establishment of the reserve, each community in the area had some local associations which regulated the use of resources at community level, however their operations were subjected to central governments decisions.…”
Section: Introductionmentioning
confidence: 99%
“…Started in 2014, the process of the designation of the reserve funded by the Federal Ministry for the Environment, Nature Conservation, Construction and Nuclear Safety of the Federal Republic of Germany was completed in 2017 with the delineation and recognition of the reserve as UNESCO Man and Biosphere Reserve (MAB). One of the reasons underlying the creation of the MTBR was the conservation and the sustainable use of its coastal resources in order to attain coastal resilience, with a focus on mangroves which had lost 93% of their coverage in the area between 1980 and 2015 [7]. Though the reserve brings together a mosaic landscape and ecosystems of the southern Benin and Togo into a unique protected environment, the management of its natural resources remains country specific.…”
Section: Introductionmentioning
confidence: 99%